Effects of Terrestrial Buffer Zones on Amphibians on Golf Courses - Puglis, Holly J.; Boone, Michelle D. (PLOS ONE, 2012)
A major cause of amphibian declines worldwide is habitat destruction or alteration. Public green spaces, such as golf courses and parks, could serve as safe havens to curb the effects of habitat loss if managed in ways to bolster local amphibian communities. We reared larval Blanchard's cricket frogs (Acris blanchardi) and green frogs (Rana clamitans) in golf course ponds with and without 1 m terrestrial buffer zones, and released marked cricket frog metamorphs at the golf course ponds they were reared in. Larval survival of both species was affected by the presence of a buffer zone, with increased survival for cricket frogs and decreased survival for green frogs when reared in ponds with buffer zones. No marked cricket frog juveniles were recovered at any golf course pond in the following year, suggesting that most animals died or migrated. In a separate study, we released cricket frogs in a terrestrial pen and allowed them to choose between mown and unmown grass. Cricket frogs had a greater probability of using unmown versus mown grass. Our results suggest that incorporating buffer zones around ponds can offer suitable habitat for some amphibian species and can improve the quality of the aquatic environment for some sensitive local amphibians.